Prevalence and change in social inequalities in physical activity before and during the COVID-19 pandemic in Sweden - Frida Brattlöf; Per E. Gustafsson; Miguel San Sebastián (BMC, 2023)
Abstract Background Physical activity is crucial for our wellbeing. Since the COVID-19 pandemic emerged, physical activity behaviour has changed globally, and social inequalities that already exist in physical activity have increased. However, there is limited knowledge of how these inequalities have evolved in Sweden. Thus, the aim of this study was to assess the prevalence of physical activity, and the socioeconomic inequalities in physical activity before and during the COVID-19 pandemic. Methods This study analysed data from the national 'Health on Equal Terms' survey which was conducted on participants between 16 and 84, through a repeated cross-sectional design in 2018 (pre-pandemic) and 2021 (during the pandemic). The socioeconomic variables included gender, age, education, occupation, income, and place of birth. For both years, the prevalence of low physical activity, the absolute risk differences, the slope index of inequality, and the slope index difference for each of the variables were calculated. Results The level of physical activity increased for the total population studied. However, the social inequalities that existed in 2018 increased over time and across age, education, occupation, income, and place of birth, but not with regard to gender. Conclusions Even though the Swedish population increased their levels of physical activity during the COVID-19 pandemic, the social inequalities that already existed in physical activity increased. Interventions to increase the level of physical activity among the young, people with low socioeconomic status, and those born outside Sweden are needed to reduce these social inequalities, and to improve the Swedish population's wellbeing.